Social isolation, loneliness and return migration: Evidence from older Irish adults - Alan Barrett; Irene Mosca (Institute for the Study of Labor (IZA), 2012)
Across the subjects of economics, sociology and demography, much has been written about the difficulties faced by immigrants. However, much less attention has been paid to the re-adjustment challenges migrants face on their return. In this paper, we examine whether and the extent to which a group of returned migrants experience higher degrees of social isolation and loneliness compared to compatriots who never lived abroad. The data used are from the first wave of the Irish Longitudinal Study on Ageing (TILDA). We find that social isolation is a significant feature of the lives of return migrants.
urn:nbn:de:101:1-2012042311372
Keywords: F22; J61; 330; immigrants; social isolation; loneliness; Rückwanderung; Soziale Isolation; Irland